Factors Causing Delays in Submitting Inpatient BPJS Claims at RSU dr. H. Koesnadi Bondowoso - Nuraini, Novita; Damayani, Desnia Sindi; Wijayanti, Rossalina Adi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The submission of BPJS claims by health care facilities according to the technical verification manual is at least on the 10th of the following month. Meanwhile, in October 2019, the process of submitting inpatient BPJS claims at RSU dr. H. Koesnadi Bondowoso exceeded the 10th of the next month which was 130 days delayed. The purpose of this study analyzes the factors that cause the delays in submitting inpatient BPJS claims. The Type of qualitative research by finding out causal factors based on personal factors, leadership factors, team factors, system factors and contextual/situational factors using Problem Tree Analysis. Data collection techniques are in-depth interviews, observation, documentation and brainstorming. The results showed a lack of knowledge related to the deadline for submitting a BPJS claim and a delay in file submission from inpatient rooms. Incomplete files for inpatient BPJS, internal verifier have multiple jobs and lack of guidance from chief nurse also causes of delay in submitting claims. There are no standard operating procedures, hospital information management system and scanner error, an increase of workload, and less supportive of work environment due to the Covid-19 pandemic. It is recommended to make standard operating procedures for submitting inpatient BPJS claims, discipline the employees, give rewards and add more employees for the Controller Installation.Abstrak: Pengajuan klaim BPJS oleh fasilitas pelayanan kesehatan berdasarkan buku petunjuk teknis verifikasi maksimal tanggal 10 bulan berikutnya. Proses pengajuan klaim BPJS rawat inap di RSU dr. H. Koesnadi mengalami keterlambatan dimana pengajuan bulan Oktober 2019 melebihi tanggal 10 bulan berikutnya yaitu terlambat 130 hari. Tujuan penelitian ini menganalisis faktor yang menyebabkan keterlambatan pengajuan klaim BPJS rawat inap. Jenis Penelitian kualitatif dengan mencari faktor penyebab berdasarkan personal factors, leadership factors, team factors, system factors dan contextual/situational factors menggunakan Problem Tree Analysis. Teknik pengumpulan data dengan wawancara mendalam, observasi, dokumentasi dan brainstorming. Hasil penelitian menunjukkan penyebab keterlambatan pengajuan klaim BPJS rawat inap yaitu kurangnya pengetahuan batas tanggal pengajuan klaim BPJS rawat inap, keterlambatan setor berkas klaim BPJS rawat inap dari ruangan, ketidaklengkapan berkas klaim BPJS rawat inap, verifikator internal double job, kurangnya bimbingan Kepala Ruangan, kerja sama belum maksimal, belum adanya SOP, SIMRS dan scanner eror dan beban kerja bertambah serta lingkungan kerja kurang mendukung karena pandemic Covid-19. Solusi yang dapat dilakukan yaitu membuat SOP pengajuan klaim BPJS rawat inap, pendisiplinan petugas, pemberian reward dan menambah petugas di Instalasi Pengendali.